Physiological Measures of Dopaminergic and Noradrenergic Activity During Attentional Set Shifting and Reversal - Pajkossy, Péter; Szőllősi, Ágnes; Demeter, Gyula; Racsmány, Mihály (Frontiers in Psychology, 2018)
Dopamine (DA) and noradrenaline (NA) are important neurotransmitters, which are suggested to play a vital role in modulating the neural circuitry involved in the executive control of cognition. One way to investigate the functions of these neurotransmitter systems is to assess physiological indices of DA and NA transmission. Here we examined how variations of spontaneous eye-blink blink rate and pupil size, as indirect measures of DA and NA activity, respectively, are related to performance in a hallmark aspect of executive control: attentional set shifting. We used the Intra/Extradimensional Set Shifting Task, where participants have to choose between different compound stimuli while the stimulus-reward contingencies change periodically. During such rule shifts participants have to refresh their attentional set while they reassess which stimulus-features are relevant. We found that both eye-blink rate and pupil size increased after rule shifts, when explorative processes are required to establish stimulus-reward contingencies. Furthermore, baseline pupil size was related to performance during the most difficult, extradimensional set shifting stage, whereas baseline eye-blink rate was associated with task performance prior to this stage. Our results support a range of neurobiological models suggesting that the activity of DA and NA neurotransmitter systems determines individual differences in executive functions, possibly by regulating neurotransmission in prefrontal circuits. We also suggest that assessing specific, easily accessible indirect physiological markers, such as pupil size and blink rate, contributes to the comprehension of the relationship between neurotransmitter systems and executive functions.